Proceedings of the Seventeenth International Conference on Principles of Knowledge Representation and Reasoning 2020
DOI: 10.24963/kr.2020/38
|View full text |Cite
|
Sign up to set email alerts
|

Containment of Simple Conjunctive Regular Path Queries

Abstract: Testing containment of queries is a fundamental reasoning task in knowledge representation. We study here the containment problem for Conjunctive Regular Path Queries (CRPQs), a navigational query language extensively used in ontology and graph database querying. While it is known that containment of CRPQs is EXPSPACE-complete in general, we focus here on severely restricted fragments, which are known to be highly relevant in practice according to several recent studies. We obtain a detailed overview of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…GPML's graph patterns extend the celebrated language of Conjunctive Regular Path Queries (CRPQ) introduced in [17] and studied in a plethora of follow-up work (e.g. [9,10,[14][15][16]22]). CRPQs consist of variables (typically binding only to individual vertices and edges), path patterns specified by regular expressions over the edge labels, and comma-separated lists thereof.…”
Section: Keep Any Shortestmentioning
confidence: 99%
“…GPML's graph patterns extend the celebrated language of Conjunctive Regular Path Queries (CRPQ) introduced in [17] and studied in a plethora of follow-up work (e.g. [9,10,[14][15][16]22]). CRPQs consist of variables (typically binding only to individual vertices and edges), path patterns specified by regular expressions over the edge labels, and comma-separated lists thereof.…”
Section: Keep Any Shortestmentioning
confidence: 99%
“…Calvanese et al [13] extended CRPQs to include an inverse operator, and showed that query containment is EXPSPACE-complete for this class of queries. More recently, Figuera et al [23] show that, by considering various sub-classes of CRPQs which are known to occur frequently in practice, the complexity of deciding containment can be reduced.…”
Section: Uery Containmentmentioning
confidence: 99%
“…introduced in [17] and studied in a plethora of follow-up work (e.g. [9,10,[14][15][16]22]). CRPQs consist of variables (typically binding only to individual vertices and edges), path patterns specified by regular expressions over the edge labels, and comma-separated lists thereof.…”
Section: Keep Any Shortestmentioning
confidence: 99%